Komunikasi Interpersonal Media Sosial Di Era Digital:Tantangan Dan Peluang - Salwa salsabila; Melin andila; Afwan syahril (GLOBAL SCIENTS PUBLISHER, 2025)
In the digital era dominated by social media, interpersonal communication has undergone significant transformation. This study aims to explore the challenges and opportunities that arise in interpersonal communication within the digital environment through a literature review. By analyzing various academic sources, articles, and case studies, this research identifies key aspects that influence human interaction, including changes in how individuals communicate, the impact of social media platforms on social relationships, and the dynamics of privacy and trust. The results indicate that social media can be a tool for strengthening connections, but it also presents risks such as misinterpretation and the reduction of communication depth. This study concludes that a deeper understanding of interpersonal communication in the digital era is essential to optimize social interactions and address the challenges present. It is hoped that these findings will serve as a foundation for further research and the development of effective communication strategies in the digital age